2022
DOI: 10.1039/d2nr01550a
|View full text |Cite
|
Sign up to set email alerts
|

Conjugating AIE-featured AuAg nanoclusters with highly luminescent carbon dots for improved visible-light-driven antibacterial activity

Abstract: Metal nanoclusters (NCs) have emerged as a novel antibacterial agent featuring broad-spectrum antibacterial activity without drug resistance for bacteria, but suffer from fast antibacterial invalidation due to the consumption by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…[16][17][18][19][20] For example, as is well known, the absorption peaks of CDs are mainly in the UV and visible light regions. [21][22][23] Then, our groups utilized a large amount of nitrogen source to broaden the CDs' absorption from UV-Vis to the first NIR window region (650-900 nm), which opened a new potential application as a photothermal agent in photothermal therapy. 24,25 Experimentally, the first NIR absorption window was probably attributed to the nitrogen functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] For example, as is well known, the absorption peaks of CDs are mainly in the UV and visible light regions. [21][22][23] Then, our groups utilized a large amount of nitrogen source to broaden the CDs' absorption from UV-Vis to the first NIR window region (650-900 nm), which opened a new potential application as a photothermal agent in photothermal therapy. 24,25 Experimentally, the first NIR absorption window was probably attributed to the nitrogen functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Yuan and Zhu et al reported improved antibacterial activity in a photosensitizer obtained from the conjugation of AIE-active orange-emissive AuAg NCs derived from HAuCl 4 , AgNO 3 , and glutathione, with blue-emitting carbon dots made of branched polyethylenimine and citric acid. 172 Introduction of the latter helped enhance visible lightharvesting ability, charge and energy transfer process, and photostability. This helps create a synergy between the two components which facilitate the large production of ROS under visible light irradiation.…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%
“…Metal nanoclusters (NCs) with atomic precision constitute a special class of nanomaterials due to their well-defined crystal structures, unique physicochemical properties and attractive structure-property correlations and are promising candidates for catalysis, optics, biotechnology and so on. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Among them, alloy metal NCs containing at least two different metals often lead to the enhancement of the desired properties due to their synergistic effect, 9,18,19 showing that alloying is an effective method to regulate the structure and properties of monometallic nanoclusters.…”
Section: Introductionmentioning
confidence: 99%